2023
DOI: 10.1111/jpm.12918
|View full text |Cite
|
Sign up to set email alerts
|

Accompanying mental health problems at home: Preliminary data from a crisis resolution and home treatment team in Catalonia

Abstract: Accessible SummaryWhat is known on the subject? Home treatment teams help people in a mental health crisis to recover. The staff goes to the person's home, avoiding the need to go to the hospital and providing care in the person's environment. The teams have been created in our country in recent years, becoming part of the mental health care network. What this paper adds to existing knowledge? The paper presents the functioning of a CRHTT, the type of care it provides, and the coordination with the rest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The nonsignificant change for items 11 and 12 (problems with living conditions, occupation, and activities) was expected for this patient group during crisis treatment for a few weeks. The HoNOS total sum change pre to post was above the outcome measured in a previous pre-post study of Norwegian CRTs [ 10 ] and in line with a UK randomized controlled trial [ 31 ] and two recent pre-post studies from Spain [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The nonsignificant change for items 11 and 12 (problems with living conditions, occupation, and activities) was expected for this patient group during crisis treatment for a few weeks. The HoNOS total sum change pre to post was above the outcome measured in a previous pre-post study of Norwegian CRTs [ 10 ] and in line with a UK randomized controlled trial [ 31 ] and two recent pre-post studies from Spain [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 82%
“…An earlier pre-post study of CRTs in Norway found moderate improvement in mental health [ 10 ]. Two recent pre-post studies of CRT patients in Spain also found significant improvement in psychiatric problems [ 11 , 12 ], and a recent prospective observational study of CRT patients in Greece found improvement in clinician-rated psychiatric problems pre-post and compared to treatment as usual [ 13 ]. While some studies indicate that CRT home treatment is not associated with an increased risk of violence or suicide, an extensive recent overview of various approaches in acute psychiatric care states that ‘crisis assessment at home is not suitable when someone requires urgent medical tests or treatment (for example, following an overdose or other self‐harm)’ [ 14 ].…”
Section: Introductionmentioning
confidence: 99%